Non-Identical Stanza of V. V. Nabokov in Context of Russian Verse of 19th—20th Centuries - O. S. Laletina; E. V. Khvorostjanova (Научный диалог, 2022)
The article deals with the problem of correlation between tradition and experiment in the system of verse by V. V. Nabokov. The subject of the study is the specifics of non-identical stanzas, which until now have been considered by literary critics as simple and traditional forms of Nabokov’s verse. The corpus of non-identical stanza poems was compiled as a result of the analysis of all available Russian-language texts by Nabokov: 78 non-identical stanza texts were identified in 658 monometric works, links of polymetric compositions, summary forms. It has been established that 74 models of verse (combinations of poetic meters and stanza schemes) are implemented in them. The analysis of signs of non-identity of stanzas was carried out: differences in the number of lines, rhyming, catalectics, metrical structure were recorded. It is determined that the most typical for the poet is the discrepancy between the rhyme scheme and the type of endings. The composition of the texts is described: the proportions and specificity of the structure of regular and irregular stanzas are characterized. As a result of comparing the obtained data with data on the verses of 22 Russian poets of the 19th-20th centuries, it is proved that Nabokov’s non-identical stanzas are experimental in nature, are among the forms that determine the originality of the poet’s work in the context of the Russian literary tradition.